2005
DOI: 10.1128/jcm.43.5.2407-2417.2005
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing of Streptococcus uberis Provides Sensitive and Epidemiologically Relevant Subtype Information and Reveals Positive Selection in the Virulence Gene pauA

Abstract: Control of the bovine mastitis pathogen Streptococcus uberis requires sensitive and epidemiologically meaningful subtyping methods that can provide insight into this pathogen's epidemiology and evolution. Development of a multilocus sequence typing (MLST) scheme based on six housekeeping and virulence genes allowed differentiation of 40 sequence types among 50 S. uberis isolates from the United States (n ‫؍‬ 30) and The Netherlands (n ‫؍‬ 20). MLST was more discriminatory than EcoRI or PvuII ribotyping and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 58 publications
3
60
1
Order By: Relevance
“…On the other hand, some isolates that were apparently clustered by PFGE may have different patterns of virulence genes, as illustrated in clusters VI, VII, VIII, XI, XII, XIII, and XVI ( Figure 3). Similar to this finding, Reinoso et al previously demonstrated a variation of virulence gene profiles among S. uberis isolates presenting identical PFGE patterns (30). This finding suggests that interpretation of genetic relatedness using only DNA banding pattern-based typing methods, such as PFGE, should be cautious, and genetically related isolates may not necessarily have identical functional genotypes or phenotypes.…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, some isolates that were apparently clustered by PFGE may have different patterns of virulence genes, as illustrated in clusters VI, VII, VIII, XI, XII, XIII, and XVI ( Figure 3). Similar to this finding, Reinoso et al previously demonstrated a variation of virulence gene profiles among S. uberis isolates presenting identical PFGE patterns (30). This finding suggests that interpretation of genetic relatedness using only DNA banding pattern-based typing methods, such as PFGE, should be cautious, and genetically related isolates may not necessarily have identical functional genotypes or phenotypes.…”
Section: Discussionsupporting
confidence: 76%
“…In developing the MLST in this study, target genes were selected based on the complete genome sequence of S. mutans UA159 (1) and the ongoing complete genome sequencing of S. mutans NN2025 in our laboratories, on the genomic information from other bacteria, and on the published MLST schemes for other streptococci, such as S. pyogenes (4), S. uberis (44), S. suis (13), and S. pneumoniae (3), together with their locations in the genome. Finally, eight housekeeping genes were selected for this study.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA was resuspended with 50 µl of TE buffer and then stored at 20 C. Six housekeeping and virulence genes were chosen for MLST. Primers for amplification of cpn60, pauA, oppF, sodA, and tuf were taken from the literature (Zadoks et al, 2005). For gapC, DNA sequence data from GenBank were used to design primers.…”
Section: S Uberis Isolates Collection and Identificationmentioning
confidence: 99%
“…The method relies on the sequencing of internal fragments of certain genes. To our knowledge, 2 MLST schemes have been used to investigate genetic diversity of S. uberis, one based on the sequencing of 6 housekeeping genes and virulence genes (Zadoks et al, 2005) and the other based on the sequencing of 7 housekeeping genes (Coffey et al, 2006) (http://pubmlst. org/suberis/).…”
mentioning
confidence: 99%